"I was raped inside, being in a place where I was supposed to be taken care of": Experiences of oppression and violence in health contexts towards women with disabilities and approaches from feminist occupational therapy - Yupanqui Concha, Andrea; Hichins Arismendi, Melissa Andrea; Mandiola Godoy, Daniela Inés (My University, 2022)
Introduction: The practices of violence in health contexts constitute one of the multiple manifestations of violence against women with disabilities. In Chile, as in the rest of the world, the development of studies on this violence is still incipient. Objectives: To characterize practices of violence against women with disabilities in health contexts, and to characterize experiences of vindication of human rights of this group of women in Chile, from the voices of activists and professional occupational therapists. Method: A secondary analysis of qualitative data from a study executed between 2015 and 2020 was conducted. From a qualitative approach and collective case study, a secondary thematic analysis of the data obtained from 8 interviewees was performed. Results: From the perspective of the informants, women with disabilities experience structural violence in a systematic and transversal way, which crosses other various forms of violence: physical, psychological, sexual, obstetric, and symbolic-institutional. The experiences of this group in daiming their human rights reflect processes of emancipation, resistance, and construction of practices that transform these violations. Conclusion: The practices of violence in health contexts toward women with disabilities in Chile is a situation visualized as manifestations of domination and oppression against them, which perpetuate their social exclusion and inequalities in health. Faced with this situation of social injustice, women activists and professional occupational therapists propose the need to implement strategies for the vindication of human rights, together with practices of collective resistance.
Keywords: violence against women; women's health; women's rights; occupational therapy